Factors Affecting Capital Structure of Conventional and Islamic Banks: Evidence from MENA Region - Ahmad Al-Harby (Global Review of Islamic Economics and Business, 2019)
This study aim is to investigate and compare the factors affecting conventional and Islamic bank’s capital structure choice as well as their financial characteristics. According to the best of my knowledge, this is the first paper that mainly concentrated in comparing the determinants of capital structure of conventional and Islamic banks using a cross-country data and for a long period of time (20 years). The study revealed several findings. Firstly, descriptive statistics (equality of means test) showed that conventional banks more leveraged and liquid than Islamic banks. In contrast, Islamic banks are larger and more profitable (ROA) than conventional banks. The results also indicated that Islamic banks are not riskier than conventional banks. Secondly, the regression results showed that all variables, except tax-shield, had the same impact on both banking types capital structure. It been found that profitability, tangibility, business risk and age correlated negatively and significantly with capital structure. In the other direction, size, liquidity and inflation had significant and positive relation with capital structure. Vis-à-vis tax-shield, this variable had a weak impact (positive) on Islamic bank’s capital structure but had no effect on conventional banks and this attributed to Islamic banks sample.